Spinal needles versus conventional needles for fine-needle aspiration biopsy of thyroid nodules—A multicenter randomized controlled trial - Kasper Daugaard Larsen; Gitte Bjørn Hvilsom; Tobias Vennervald Andersen; Preben Homøe; Finn Noe Bennedbæk; Jens Pedersen; Lena Bjergved Sigurd; Jens Jessen Warm; Katalin Kiss; Giedrius Lelkaitis; Luise Andersen; Marie Røsland Rosenørn; et al. (PLoS ONE, 2025)
Objective Ultrasound-guided fine-needle aspiration biopsy (FNAB) is essential for evaluating thyroid nodules but often yields inadequate samples, leading to repeated procedures, increased discomfort, and higher costs. Previous non-randomized studies found promising results of spinal needles to improve diagnostic adequacy. Therefore, we conducted a multicenter randomized controlled trial to validate these findings. Methods Between July 1st, 2021, and April 13th, 2023, patients with suspicious thyroid nodules were randomized to receive FNAB with either a 25G spinal needle or conventional needle. The primary outcome was the rate of adequate diagnostic cytology. Secondary outcomes included procedure-related pain, sensitivity and specificity of FNAB, and adverse events. Results A total of 359 patients (75.6% female), with a mean age of 59.7 years (range 23−94) were randomized. The rate of adequate diagnostic FNAB was 86.2% (156/181) for the spinal group compared to 84.8% (151/178) for the control group (OR 1.01; 95% CI: 0.95–1.08). The mean pain scale score was 4.0 (SD = 1.8) in the spinal group and 3.9 (SD = 2.0) in the control group (p = 0.40). No complications were observed in either group. We found a significantly better cytological adequacy rate of FNABs performed by physicians with more than four years of experience in the procedure (OR=1.07; 95% CI, 1.01–1.14). Conclusions No significant improvement was found using spinal needles with a stylet compared to conventional needles. Given the significantly higher cost of spinal needles and comparable diagnostic outcomes, their routine use for thyroid FNAB is not recommended.